Enhancing Employee Performance through Competence, Motivation, and Transformational Leadership: The Strategic Role of Employee Engagement - Alfi Fauzi Fadhilah; Asti Nur Aryanti; Nunung Ayu Sofiati; Gurawan Dayona Ismail; Ridlwan Muttaqin (MASI Mandiri Edukasi, 2026)
Businesses in the tourism services industry must possess superior, competitive human resources due to increasingly intense competition. Employee performance plays a crucial role in business success, particularly in the service sector, which is highly dependent on service quality. This study aims to examine the effects of service competence, work motivation, and transformational leadership on employee performance at PT HAS Nawara Nusantara, with employee engagement serving as a mediating variable. This research employs a quantitative, survey-based approach. Data were collected through questionnaires distributed to employees of PT HAS Nawara Nusantara who had worked at the company for at least 1 year. Both direct and indirect relationships among variables were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that employee engagement is positively and significantly influenced by service competence, work motivation, and transformational leadership. Furthermore, employee engagement has a positive and significant effect on employee performance, whereas service competence and work motivation do not have a significant direct effect on employee performance. Employee engagement serves as a mediating variable in the relationships among service competence, work motivation, transformational leadership, and employee performance. In conclusion, companies can implement human resource development strategies by enhancing service competence, strengthening work motivation, and applying transformational leadership to foster high and sustainable employee engagement.